Jeroky: gesture of a philosophical body and a creative process in dance (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This paper is an elaborations on the idea of jeroky (Papá,2021) — a Guarani word used to express dance. Nevertheless, it brings a different meaning from the Western experience. Having the espantographic exercise (Pucheu, 2021) as methodological operator. The espantografy — the writing born from the awe — is understood as a linguistic performative act where the divisions of music, poetry, philosophy, performance and dance become a single flux of embodied gestures. Arguing that a (philosophical and poetic) posture that gives floor to the awe and the surprise. This work presents a perspective to creative processes in dance, holding in jeroky as a way of acting and thinking in the performance Pomo (2012).
Keywords: philosophy; poetry; dance; embodiment.; Jeroky